Role of community nursing during the first 1000 days of life - Hidalgo Tapia, Esthela Carolina (2023)
The objective of this essay is to analyze the role of community nursing during the first 1000 days of life. During the first 1000 days of life, the formation of most of the organs, tissues, as well as the physical and intellectual abilities of the person occurs, if it is not developed adequately, there is the possibility of generating irreversible damage that will affect their quality of life. Therefore, community nursing is responsible for the health care of the mother and child from the pre- and postnatal period, focusing on nutrition, breastfeeding, complementary feeding, hygiene, education and home care to promote an adequate process. growth and development of the child.